2015
DOI: 10.3109/17453674.2015.1012975
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the risk of revision in cementless total hip arthroplasty with ceramic-on-ceramic and metal-on-polyethylene bearings

Abstract: Background and purpose Ceramic-on-ceramic (CoC) bearings were introduced in total hip arthroplasty (THA) to reduce problems related to polyethylene wear. We compared the 9-year revision risk for cementless CoC THA and for cementless metal-on-polyethylene (MoP) THA.Patients and methods In this prospective, population-based study from the Danish Hip Arthroplasty Registry, we identified all the primary cementless THAs that had been performed from 2002 through 2009 (n = 25,656). Of these, 1,773 THAs with CoC beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
(45 reference statements)
1
35
1
Order By: Relevance
“…This is an important finding because the time to revision of CoC THA was not mentioned in previous studies [27] or easy to extract from registries (the Australian register mentioned 2109 of 65,114 CoC THA revisions [3.2%] but not the revision rate before 5 years) [32]. Our results are in accordance with the Danish register indicating that 63 of 71 (88%) CoC THAs were revised before 5 years of followup [35]. This issue suggests that CoC THAs are technically demanding to use [26].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is an important finding because the time to revision of CoC THA was not mentioned in previous studies [27] or easy to extract from registries (the Australian register mentioned 2109 of 65,114 CoC THA revisions [3.2%] but not the revision rate before 5 years) [32]. Our results are in accordance with the Danish register indicating that 63 of 71 (88%) CoC THAs were revised before 5 years of followup [35]. This issue suggests that CoC THAs are technically demanding to use [26].…”
Section: Discussionsupporting
confidence: 82%
“…We cannot explain the higher rate of CoC THA revision because of infection (OR, 1.63 [1.12-2.37] versus MoP) despite this complication being mostly observed after large-diameter head MoM revisions [36]. Our study reported 39 of 238 revisions because of infection (16%), whereas the Danish hip register reports only 8% (six of 71) [35] and the Australian register less than 1% cumulative incidence revision because of infection at 10 years [32]. These infections were observed in our study despite the CoC population being younger and more active than the MoP group.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In 2015, four ongoing PhD students are using data from the DHR. They have identified the “true” incidence of prosthetic joint infection,11 described the epidemiology and outcome of fast track setting in Denmark,12 found that ceramic-on-ceramic does not have a greater risk of revision compared to metal-on-polyethylene bearings,13 and identified cirrhosis as a risk factor for postoperative complications 14…”
Section: Resultsmentioning
confidence: 99%
“…The main cause of revision for CoC THA was dislocation (1.2%), and for MoM THA it was aseptic loosening (1.9%) (Varnum et al. 2015a, b). As survival and causes of revision differed for different types of bearings, one could also ask whether patient-reported outcomes (PROs) would be different for different bearings in THA.…”
mentioning
confidence: 99%